[18F]FluorThanatrace ([18F]FTT) PET Imaging of PARP-Inhibitor Drug-Target Engagement as a Biomarker of Response in Ovarian Cancer, a Pilot Study - Pantel, Austin R.; Gitto, Sarah B.; Makvandi, Mehran; Kim, Hyoung; Medvedv, Sergey; Weeks, Joanna K.; Torigian, Drew A.; Hsieh, Chia-Ju; Ferman, Benjamin; Latif, Nawar A.; Tanyi, Janos L.; Martin, Lainie P.; et al. (Clinical cancer research, 2023)
PARP inhibitors have become the standard-of-care treatment for homologous recombination deficient (HRD) high-grade serous ovarian cancer (HGSOC). However, not all HRD tumors respond to PARPi. Biomarkers to predict response are needed. [18F]FluorThanatrace ([18F]FTT) is a PARPi-analog PET radiotracer that noninvasively measures PARP-1 expression. Herein, we evaluate [18F]FTT as a biomarker to predict response to PARPi in patient-derived xenograft (PDX) models and subjects with HRD HGSOC. In PDX models, [18F]FTT-PET was performed before and after PARPi (olaparib), ataxia-telangiectasia inhibitor (ATRi), or both (PARPi-ATRi). Changes in [18F]FTT were correlated with tumor volume changes. Subjects were imaged with [18F]FTT-PET at baseline and after ∼1 week of PARPi. Changes in [18F]FTT-PET uptake were compared with changes in tumor size (RECISTv1.1), CA-125, and progression-free survival (PFS). A decrease in [18F]FTT tumor uptake after PARPi correlated with response to PARPi, or PARPi-ATRi treatment in PARPi-resistant PDX models (r = 0.77-0.81). In subjects (n = 11), percent difference in [18F]FTT-PET after ∼7 days of PARPi compared with baseline correlated with best RECIST response (P = 0.01), best CA-125 response (P = 0.033), and PFS (P = 0.027). All subjects with >50% reduction in [18F]FTT uptake had >6-month PFS and >50% reduction in CA-125. Utilizing only baseline [18F]FTT uptake did not predict such responses. The decline in [18F]FTT uptake shortly after PARPi initiation provides a measure of drug-target engagement and shows promise as a biomarker to guide PARPi therapies in this pilot study. These results support additional preclinical mechanistic and clinical studies in subjects receiving PARPi ± combination therapy. See related commentary by Liu and Zamarin, p. 1384.